2010
DOI: 10.1177/0899764010380927
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Empirical Studies of Philanthropy

Abstract: We thank the audiences for helpful comments and suggestions. Thanks to various colleagues who provided articles we could not find and who clarified their findings. We thank the editor and two anonymous referees of NVSQ for useful comments. Thanks to Esra Dursun and Barry Hoolwerf for research assistance.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
881
1
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,071 publications
(1,001 citation statements)
references
References 337 publications
43
881
1
15
Order By: Relevance
“…Secondly, empirical work on tipping, donations, customer gifts and trust-/ honor-based billing variants was not included, because these four voluntary market payment mechanisms differ in terms of important attributes from the PWYW price setting approach (see Figure 1). Apart from that, excellent research reviews for these participative, voluntary payment procedures are already available (Azar, 2007;Bekkers and Wiepking, 2011;Natter and Kaufmann, 2015;Schlüter and Vollan, 2015). Thirdly, we excluded laboratory studies of so-called "dictator games" in which individuals act as payers or recipients of money (see the reviews of Engel, 2011;Mousazadeh and Izadkhah, 2015).…”
Section: Study Identification and Selection Proceduresmentioning
confidence: 99%
“…Secondly, empirical work on tipping, donations, customer gifts and trust-/ honor-based billing variants was not included, because these four voluntary market payment mechanisms differ in terms of important attributes from the PWYW price setting approach (see Figure 1). Apart from that, excellent research reviews for these participative, voluntary payment procedures are already available (Azar, 2007;Bekkers and Wiepking, 2011;Natter and Kaufmann, 2015;Schlüter and Vollan, 2015). Thirdly, we excluded laboratory studies of so-called "dictator games" in which individuals act as payers or recipients of money (see the reviews of Engel, 2011;Mousazadeh and Izadkhah, 2015).…”
Section: Study Identification and Selection Proceduresmentioning
confidence: 99%
“…Bowman (2006) reports that changes in overhead ratios communicate useful information to donors. Bekkers and Wiepking (2011) identify overhead costs as important factor influencing charitable giving as fundraising costs impact on donors' confidence on the campaign (e.g., Sargeant, Ford, and West, 2006). Gneezy, Keenan, and Gneezy (2014) found that informing potential donors of low overhead costs increased donation rates.…”
Section: Introductionmentioning
confidence: 99%
“…Yet donors face another source of uncertainty: the donation may miss its stated purpose. This relates to the efficacy motive of Bekkers and Wiepking (2011):942: the perception of donors that their contribution makes a difference to the cause they are supporting. The money that was meant to help the victims of a natural disaster ends up in the pockets of local warlords.…”
Section: Introductionmentioning
confidence: 99%
“…They are willing to give up money and donate to charitable organizations. Bekkers and Wiepking (2011) reviewed over 500 articles on charitable giving and identified eight mechanisms as the most important forces that drive charitable giving: (a) awareness of need; (b) solicitation; (c) costs and benefits; (d) altruism; (e) reputation; (f) psychological benefits; (g) values; and (h) efficacy. They define charitable giving as the donation of money to an organization that benefits others beyond one's own family, a definition we follow.…”
Section: Introductionmentioning
confidence: 99%